2019
DOI: 10.2903/j.efsa.2019.5658
|View full text |Cite
|
Sign up to set email alerts
|

Safety of betaine as a novel food pursuant to Regulation (EU) 2015/2283

Abstract: In 2017, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) concluded that betaine as a novel food (NF) is safe to be used at a maximum intake level of 6 mg/kg body weight per day in addition to the intake from the background diet. Following the present request from the European Commission, the EFSA NDA Panel was asked to deliver a scientific opinion on betaine by carrying out the assessment for the revised uses and use levels of betaine as proposed by the applicant. Thus, EFSA performed an inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In a few cases, food additives (e.g., soy lecithin in beta-lactoglobulin) or bulking agents (e.g., maltodextrin in xylo-oligosaccharides (XOS)) are added into the final formulation of the NF for technological purposes. The end-products are commercialized in powder form (i.e., Galactooligosaccharides (GOS), as (concentrated) syrups/liquids (cocoa pulp), crystals (anhydrous or monohydrate betaine), or dried whole products (coffee husk (cascara) and coffee cherry pulp)) ( 23–27 , 29–32 , 36 ).…”
Section: Overview Of the Common Key Scientific Requirements For The S...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a few cases, food additives (e.g., soy lecithin in beta-lactoglobulin) or bulking agents (e.g., maltodextrin in xylo-oligosaccharides (XOS)) are added into the final formulation of the NF for technological purposes. The end-products are commercialized in powder form (i.e., Galactooligosaccharides (GOS), as (concentrated) syrups/liquids (cocoa pulp), crystals (anhydrous or monohydrate betaine), or dried whole products (coffee husk (cascara) and coffee cherry pulp)) ( 23–27 , 29–32 , 36 ).…”
Section: Overview Of the Common Key Scientific Requirements For The S...mentioning
confidence: 99%
“…Nonetheless, particularly for certain NF derived from by-products, it can be challenging to collect a robust body of evidence, as a thorough characterization of the proteins contained in an NF is required. NF derived from rapeseed ( 33 ), coffee ( 25–27 ), and cacao ( 24 ), as well as betaine produced via yeast fermentation ( 29 ), are examples of NF for which the likelihood of allergic reactions was based on such body of evidence.…”
Section: Overview Of the Common Key Scientific Requirements For The S...mentioning
confidence: 99%
“…The safety of betaine in human nutrition was evaluated by the Scientific Panel on Dietetic Products, Nutrition and Allergies (NDA) in 2005, 2017 and 2019 (EFSA NDA Panel, 2005 , 2017 , 2019 ). Betaine was found to be not genotoxic on in vivo and in vitro tests.…”
Section: Assessmentmentioning
confidence: 99%
“…During both evaluations a NOAEL could not be derived from the study on chronic toxicity and carcinogenicity. Based on human intervention studies and information on highest reported mean intakes, which can sum up to 830 mg/day, an amount of 400 mg betaine per day (6 mg/kg body weight (bw) per day for adults) in addition to background exposure is considered safe by the NDA Panel (EFSA NDA Panel, 2017 , 2019 ).…”
Section: Assessmentmentioning
confidence: 99%